Share The Music : Instrument : Sounds (McGraw-Hill School Publishing Company, 1995)
Children visit an orchestra to learn about specific instruments and three methods of sound production: vibrating strings, instruments that are blown, and those that are struck. Instrumental and ensemble performances from various world cultures are also included, giving children opportunities to categorize the method of sound production used.